Rintangan Pendakwah Pada Massa Era Teknologi Digital Dan Pemanfaatannya Sebagai Media Dakwah - Dinda Rizky Amalia; Wahyu Ziaulhaq (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
Today's digital technology, which continues to experience rapid progress, is felt to be increasingly needed with the continued development of modernization in mass media as it is today. digital technology has become the era of mass industry now, so it should be used as a medium of da'wah that helps convey da'wah missions that seek to form character, morals of the nation's children who are polite and humanist according to the view of Islam. digital technology tends to market its production for business purposes only, but it must be noted together that digital technology is very helpful for da'wah interpreters to express da'wah messages. The era of digital technology is an ever-evolving borderless world that combines renewable technology with the presence of cyber technology. Digital technology has entered the level of the latest trends in the transfer of information to the public, which can also be used as a transfer of da'wah messages.